Incentives and Disincentives for the Treatment of Depression and Anxiety: A Scoping Review. (July 2014) - Ashcroft, Rachelle; Silveira, Jose; Rush, Brian; McKenzie, Kwame
Objective: There is widespread support for primary care to help address growing mental health care demands. Incentives and disincentives are widely used in the design of health care systems to help steer toward desired goals. The absence of a conceptual model to help understand the range of factors that influence the provision of primary mental health care inspired a scoping review of the literature. Understanding the incentives that promote and the disincentives that deter treatment for depression and anxiety in the primary care context will help to achieve goals of greater access to mental health care. Method: A review of the literature was conducted to answer the question, how are incentives and disincentives conceptualized in studies investigating the treatment of common mental disorders in primary care? A comprehensive search of MEDLINE, PsycINFO, CINAHL, and Google Scholar was undertaken using Arksey and O'Malley's 5-stage methodological framework for scoping reviews. Results: We identified 27 studies. A range of incentives and disincentives influence the success of primary mental health care initiatives to treat depression and anxiety. Six types of incentives and disincentives can encourage or discourage treatment of depression and anxiety in primary care: attitudes and beliefs, training and core competencies, leadership, organizational, financial, and systemic. Conclusions: Understanding that there are 6 different types of incentives that influence treatment for anxiety and depression in primary care may help service planners who are trying to promote improved mental health care.